1989
DOI: 10.1088/0266-5611/5/3/008
|View full text |Cite
|
Sign up to set email alerts
|

Solution of inverse nodal problems

Abstract: In this paper we show that the coefficients in a second-order differential equation can be determined from the positions of the nodes for the eigenfunctions. We prove uniqueness results, derive approximate solutions, give error bounds and present numerical experiments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
102
0
1

Year Published

1998
1998
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(106 citation statements)
references
References 12 publications
3
102
0
1
Order By: Relevance
“…The data indicates quadratic convergence away from the discontinuity, which is consistent with our observations in [HMcL2]. n = 5 n = 10 n = 20 n = 40 Table 2.…”
Section: Section 5: Numerical Experimentssupporting
confidence: 89%
“…The data indicates quadratic convergence away from the discontinuity, which is consistent with our observations in [HMcL2]. n = 5 n = 10 n = 20 n = 40 Table 2.…”
Section: Section 5: Numerical Experimentssupporting
confidence: 89%
“…She showed that the knowledge of a dense subset of nodal points is su¢ cient to determine the potential function of Sturm-Liouville problem up to a constant [21]. Also, some numerical results about this problem were given in [22]. Nowadays, many authors have given some interesting results about inverse nodal problems for di¤erent type operators (see [23], [24], [25], [26], [27]).…”
Section: Introductionmentioning
confidence: 99%
“…Such problems play an important role in mathematics and have many applications in natural sciences and engineering (see [1,2,15,[20][21][22]29] and the references therein). The inverse nodal problem, first posed and solved by McLaughlin [13,23], is the problem of constructing operators from given nodes (zeros) of their eigenfunctions (refer to [3][4][5]12,14,17,24,[26][27][28]). From the physical point of view this corresponds to finding, e.g., the density of a string or a beam from the zero-amplitude positions of their eigenvibrations.…”
Section: Introductionmentioning
confidence: 99%